Adaptive plasticity in plant traits increases time to hydraulic failure under drought in a foundation tree. (26th July 2021) - Challis, Anthea; Blackman, Chris; Ahrens, Collin; Medlyn, Belinda; Rymer, Paul; Tissue, David
Abstract: The viability of forest trees, in response to climate change-associated drought, will depend on their capacity to survive through genetic adaptation and phenotypic plasticity in drought tolerance traits. Genotypes with enhanced plasticity for drought tolerance (adaptive plasticity) will have a greater ability to persist and delay the onset of hydraulic failure. By examining populations from different climate-origins grown under contrasting soil water availability, we tested for genotype (G), environment (E) and genotype-by-environment (G × E) effects on traits that determine the time it takes for saplings to desiccate from stomatal closure to 88% loss of stem hydraulic conductance (time to hydraulic failure, THF). Specifically, we hypothesized that: (i) THF is dependent on a G × E interaction, with longer THF for warm, dry climate populations in response to chronic water deficit treatment compared with cool, wet populations, and (ii) hydraulic and allometric traits explain the observed patterns in THF. Corymbia calophylla saplings from two populations originating from contrasting climates (warm-dry or cool-wet) were grown under well-watered and chronic soil water deficit treatments in large containers. Hydraulic and allometric traits were measured and then saplings were dried-down to critical levels of drought stress to estimate THF. Significant plasticity was detected in the warm-dry population in response to water-deficit, with enhanced drought tolerance compared with the cool-wet population. Projected leaf area and total plant water storage showed treatment variation, and minimum conductance showed significant population differences driving longer THF in trees from warm-dry origins grown in water-limited conditions. Our findings contribute information on intraspecific variation in key drought traits, including hydraulic and allometric determinants of THF. It highlights the need to quantify adaptive capacity in populations of forest trees in climate change-type drought to improve predictions of forest die-back.